FUNDAMENTAL ANALYSIS AS A BASIS FOR INVESTMENT DECISION-MAKING WITH THE DISCOUNTED CASH FLOW (DCF) APPROACH - Ichsan, Chairil Fadhilah; Wardana, Guntur Kusuma (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The stock trend has been on the rise recently during the Covid 19 pandemic which has caused several economic sectors to decline. Some cases show that public figures who start investing and selling profits influence their social media followers and make the current generation of teenagers increasingly want to invest. Therefore, it is necessary to have an in-depth understanding of fundamental analysis in investment and what decisions should be made in investing in the Capital Market. The purpose of the research is to find out the right stock investment decisions made in companies listed on the JII70. The type of research used is quantitative research with a descriptive approach. The population in this study was 108 companies, using the purposive sampling techniq21 companies became research samples. Data was obtained from financial reports issued by the Indonesia Stock Exchange. The data analysis model uses the DCF approach. The results showed that the maximum undervalued ratio of stocks in the JII 70 Index for 2019-2021 analyzed was 86%, so investors should buy shares and increase their ownership or maintain their ownership to expect the share price to increase in the future. The stock with the largest overvalued ratio in 2019 was 43%, and the market price was higher than its fair price, so investors did not buy the stock.